Convergent Motor Patterns from Divergent Circuits - Saideman, Shari R. (J Neurosci, 2007)
Neuromodulation changes the cellular and synaptic properties of neurons, thereby enabling individual neuronal circuits to generate multiple activity patterns. However, distinct modulatory inputs could conceivably also cona different motor circuits to generate similar activity patterns. Using the isolated stomatogastric ganglion (STG) of the crab Cancer borealis, we showed previously that pyrokinin (PK) peptides activate the gastric mill (chewing) rhythm without the participation of the projection neuron modulatory commissural neuron 1 (MCN1). MCN1, which does not contain the PK peptide, also activates the gastric mill rhythm and, at these times, is a gastric mill central pattern generator (CPG) neuron. Here, we show that the gastric mill rhythms elicited by PK superfusion and MCN1 stimulation in the isolated STG are comparable, in contrast to the distinct gastric mill rhythms elicited by other input pathways. We also identified several cellular and synaptic mechanisms underlying the PK- and MCN1-elicited gastric mill rhythms that are distinct, including additional differences in their core CPG neurons. For example, the presence of the inhibitory synapse from the pyloric pacemaker neuron anterior burster onto the gastric mill CPG was necessary only for generation of the PK-elicited gastric mill rhythm. Similarly, the dorsal gastric motor neuron regulated only the PK rhythm, apparently because of PK-mediated enhancement of its synaptic actions. Thus, we demonstrate that different modulatory inputs can elicit comparable, as well as distinct activity patterns from the same neuronal ensemble. Moreover, these comparable rhythms can result from distinct CPGs using overlapping, but distinct sets of cellular and synaptic mechanisms.